ON ISOSTASY AT ATLANTIC-TYPE CONTINENTAL MARGINS - Karner, G; Watts, A (1982)
Cross-spectral techniques have been used to analyze the relationship between free air gravity anomalies and topography of approx 100 profiles over the continental margins of E North America, SW Africa, and the Coral Sea/Lord Howe Rise. The resulting admittance functions for these margins have been interpreted in terms of the flexure model of isostasy. The relatively young Coral Sea/Lord Howe rise margin is associated with the lowest value of the effective elastic thickness (Te<5km), while the relatively old E North American margin is associated with the highest value (10